Efektivitas Edukasi Praktik Sleep Hygiene Terhadap Perubahan Sikap Ibu Hamil - Pondaang, Mytha Febriany; Asih, Fransisca Retno; I’anah, Fauzah Cholashotul (POLTEKKES KEMENKES MANADO, 2023)
Background: Insomnia is a sleep disorder in pregnant women which can cause family welfare to decline if treatment is slow. Insomnia has the potential to increase the risk of preeclampsia, prematurity, childbirth section cesarean, obesity, and hyperglycemia in children. Sleep hygiene is a non-pharmacological therapy used to treat insomnia. Objective: to assess the effectiveness of practical education on sleep hygiene regarding changes in attitudes of pregnant women. Method: In this research, the research team used video media and educational flyers about sleep hygiene to find out the comparison of its influence on the attitudes of pregnant women. The method used is quasi-experimental with an approach-equivalent two-group design namely using different intervention groups, the video group, and the flyer group. Results: This research shows the increase in the attitudes of pregnant women who were given education hygiene for 18 days through animated videos was higher than providing education using flyers where the group of pregnant women who were given the intervention had better changes in attitudes towards the need for rest and sleep compared to the control group. Thus, practical education and sleep hygiene Using animated videos can be used in providing care to pregnant women, especially those experiencing sleep disorders because they can improve sleep quality so they can better deal with negative situations during pregnancy such as anxiety and insomnia.